REFRAMING EDUCATIONAL INNOVATION FOR AN INCLUSIVE AND SUSTAINABLE FUTURE: INTEGRATING TECHNOLOGY, SUSTAINABILITY AND CROSS-SECTOR COLLABORATION - Rusdiaman Rauf; Semuel Pajala; Andi Syamsul Rijal; Muhammad Firmansyah (Jurnal Review Pendidikan dan Pengajaran, 2026)
This study aims to examine how to develop an equitable and inclusive education system, analyze the transformative impact of technology on teaching and learning, identify global best practices in education for sustainable development, and explore the role of collaboration among academia, industry, and government in driving educational reform. The research employs an exploratory qualitative design by integrating an integrative literature review and comparative case study analysis, using data from academic publications, international policy reports, and relevant scholarly documents. Data were analyzed through content analysis, comparative analysis, and thematic synthesis. The findings reveal that educational innovation is essential for enhancing the quality and relevance of learning; inclusive education plays a critical role in ensuring equal access and participation; and technology significantly transforms learning into more flexible and personalized experiences, despite persistent challenges related to the digital divide. Furthermore, global best practices highlight the importance of action-oriented and sustainability-driven education. The study also finds that collaboration through the Triple Helix model effectively aligns education with labor market needs and fosters innovation. In conclusion, sustainable educational transformation requires the integrated implementation of innovation, inclusivity, technology, and cross-sector collaboration to build an adaptive, equitable, and future-oriented education system..